2010
DOI: 10.1590/s1519-69842010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Coliform accumulation in Amphibalanus amphitrite (Darwin, 1854) (Cirripedia) and its use as an organic pollution bioindicator in the estuarine area of Recife, Pernambuco, Brazil

Abstract: Samples of water and barnacles Amphibalanus amphitrite were collected from Recife, Brazil, to assess if it accumulates total (TC) and thermotolerant coliforms (TTC) related with sewage pollution. The Most Probable Number (MPN) values and the standard procedures for examination of shellfish were used. Comparatively with the water samples, the highest coliform values came from the barnacles, with TC values ranging from < 3.0 × 10 3 to ≥ 2.4 × 10 6 MPN.g -1 , and TTC ranging from ≥ 2.4 × 10 3 to 2.9 × 10 5 MPN.g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(38 reference statements)
0
5
0
2
Order By: Relevance
“…Species for biomonitoring are generally good coliform accumulators (Farrapeira et al, 2010). This indicates the importance of these microorganisms as indicators of contamination, which also extends to food.…”
Section: Discussionmentioning
confidence: 95%
“…Species for biomonitoring are generally good coliform accumulators (Farrapeira et al, 2010). This indicates the importance of these microorganisms as indicators of contamination, which also extends to food.…”
Section: Discussionmentioning
confidence: 95%
“…A presença de esgotos domésticos também foi constatada pelos altos níveis de coliformes fecais na água da região da Bacia do Pina (FEITOSA, 1988). A presença de coliformes fecais e termotolerantes foi reportada em bivalves da espécie Anomalocardia brasiliana e em crustáceos Amphibalanusamphitritena coletados dentro do estuário (Barros et al 2009;Farrapeira et al 2010). Nas áreas urbanas, esse tipo de contaminação tende a gerar um grande risco à saúde humana, tais como cólera, febre tifoide e hepatite viral, devido ao aparecimento de microorganismos patogênicos, que podem ser ingeridos pelo homem através do consumo de peixes e frutos do mar contaminados, ou ainda pelo contato com a água (VON SPERLING, 1996).…”
Section: Resultados E Discussão Estudos Realizadosunclassified
“…We compared the abundance of CB in Jiaozhou Bay with other areas worldwide (Supplementary Table 6). Farrapeira et al (2010) found that, based on MPN analysis, total coliforms in an estuary area in Brazil were more than 2.4 × 10 3 MPN/100 ml, while the abundance was 0.9 × 10 MPN/100 ml at a port station in May, 2007. Also in Brazil, Mignani et al (2013 reported that in 2007-2008, the mean abundance of CB in a cultivation area and a contaminated area was 18 and 156 MPN/100 ml, respectively.…”
Section: Dip No −mentioning
confidence: 97%
“…Furthermore, bacteria can travel and be transported some distance (Jeng et al, 2005), which could be another reason for the phenomena in the estuary and inner bay areas. In the bay mouth and outer bay areas, the exchange of seawater between Jiaozhou Bay and the open sea is greater, so pollutions may be diluted to very low concentrations, and have less influence on CB abundances as highlighted in the research of Farrapeira et al (2010). Seawater could purify itself may be another possible explanation for the spatial distribution of CB in Jiaozhou Bay.…”
Section: Dip No −mentioning
confidence: 99%